Favourable serum calcification propensity with intraperitoneal as compared with subcutaneous insulin administration in type 1 diabetes. (March 2020) - van Dijk, Peter R.; Waanders, Femke; Pasch, Andreas; Logtenberg, Susan J. J.; Vriesendorp, Titia; Groenier, Klaas H.; Hillebrands, Jan-Luuk; Kleefstra, Nanno; Gans, Rijk O. B.; van Goor, Harry; Bilo, Henk J.G.
Background: Serum calcification propensity can be monitored using the maturation time of calciprotein particles in serum (T50 test). A shorter T50 indicates greater propensity to calcify; this is an independent determinant of cardiovascular disease. As the intraperitoneal (IP) route of insulin administration mimics the physiology more than the subcutaneous (SC) route in persons with type 1 diabetes (T1DM), we hypothesized that IP insulin influences determinants of calcium propensity and therefore result in a longer T50 than SC insulin administration. Methods: Prospective, observational case-control study. Measurements were performed at baseline and at 26 weeks in age and gender matched persons with T1DM. Results: A total of 181 persons, 39 (21.5%) of which used IP and 142 (78.5%) SC insulin were analysed. Baseline T50 was 356 (45) minutes. The geometric mean T50 significantly differed between both treatment groups: 367 [95% confidence interval (CI) 357, 376] for the IP group and 352 (95% CI 347, 357) for the SC group with a difference of –15 (95% CI –25, –4) minutes, in favour of IP treatment. In multivariable analyses, the IP route of insulin administration had a positive relation on T50 concentrations while higher age, triglycerides and phosphate concentrations had an inverse relation. Conclusion: Among persons with T1DM, IP insulin administration results in a more favourable calcification propensity time then SC insulin. It has yet to be shown if this observation translates into improved cardiovascular outcomes.